1991
DOI: 10.1007/bf01606522
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of oestrogen receptors, progesterone receptors and Ki-67 in leiomyoma and myometrium during the menstrual cycle and pregnancy

Abstract: Immunohistochemical distribution of oestrogen receptors (ER), progesterone receptors (PR), and the cell proliferation-associated antigen Ki-67 was investigated in leiomyomas and the myometrium during the menstrual cycle and pregnancy. In the myometrium, ER expression was observed in the proliferative phase, but was suppressed in the secretory phase and during pregnancy. In leiomyomas, ER expression was observed throughout the menstrual cycle, but was suppressed during pregnancy. However, PR was expressed both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 15 publications
10
50
0
2
Order By: Relevance
“…This study has demonstrated wide expression of ER alpha and PR in nearly 100% of uterine LMA and low level of AR expression in the uterine tissues which were in accordance to previous studies (Kawaguchi, 1991;Leitao, 2004). Although the level of sex steroid receptors were similar in adjacent myometriums and uterine leiomyomas of all cases, AhR was strongly stained and significantly overexpressed (p=0.034, OR=1.667) in uterine LMA.…”
Section: Discussionsupporting
confidence: 91%
“…This study has demonstrated wide expression of ER alpha and PR in nearly 100% of uterine LMA and low level of AR expression in the uterine tissues which were in accordance to previous studies (Kawaguchi, 1991;Leitao, 2004). Although the level of sex steroid receptors were similar in adjacent myometriums and uterine leiomyomas of all cases, AhR was strongly stained and significantly overexpressed (p=0.034, OR=1.667) in uterine LMA.…”
Section: Discussionsupporting
confidence: 91%
“…These tumors do not only morphologically resemble uterine leiomyomas, but they also are positive for ER, which is similar to uterine leiomyomas (21,22) and dissimilar to GISTs, which are ER-negative according to our results. Therefore, ER immunostaining is a valuable aid to separate the uterine type leiomyomas from GISTs.…”
Section: Discussionsupporting
confidence: 70%
“…Average numbers of Ki-67 positive cells per cross-section in 3-to 5-mo-old WT and the transgenic mice were 1.42 ± 0.99 and 6.17 ± 2.29, respectively. Extent of mitotic activity present in the transgenic myometrium was comparable to the reported level of mitotic cells in uterine leiomyomas (31).…”
Section: Transgenic Overexpression Of Hgpr10 In Mouse Myometrium Leadsupporting
confidence: 77%